Illustrating El Cid : 1498 to today - Beck, Lauren (McGill-Queen's University Press, 2019)
"Like England's Arthur and France's Charlemagne, the Cid is Spain's national hero, and for centuries he has served as an ideal model of citizenship. All Spaniards are familiar with the story of the Cid and the multifarious ways in which he is visualized. From illuminations in medieval manuscripts to illustrations in twenty-first-century editions, depictions of the Cid vary widely, revealing just how much Spain's national identity has transformed throughout the centuries. Uncovering the racial, gendered, and political impacts of one of Spain's most legendary heroes, Illustrating El Cid, 1498 to Today traces the development of more than five centuries of illustrations and problematizes their reception and circulation in Spain and abroad. By documenting the evolution of visual representations of the Cid, their artists, and their targeted readerships, Lauren Beck also uncovers how his legend became a national projection of Spanish identity, one that was shaped by foreign hands and even manipulated into propaganda by the country's most recent dictator, Francisco Franco. Through detailed analysis, Beck unsettles the presumption that chivalric masculinity dominated the Cid's visualization, and points to how women were represented with increasing modesty as readerships became younger in modern times. An unprecedented exploration of Spanish visual history, Illustrating El Cid, 1498 to Today yields thought-provoking insights about the powerful ways in which illustration shapes representations of gender, identity, and ethnicity."--